2022
DOI: 10.1038/s41467-022-34479-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenine base editing efficiently restores the function of Fanconi anemia hematopoietic stem and progenitor cells

Abstract: Fanconi Anemia (FA) is a debilitating genetic disorder with a wide range of severe symptoms including bone marrow failure and predisposition to cancer. CRISPR-Cas genome editing manipulates genotypes by harnessing DNA repair and has been proposed as a potential cure for FA. But FA is caused by deficiencies in DNA repair itself, preventing the use of editing strategies such as homology directed repair. Recently developed base editing (BE) systems do not rely on double stranded DNA breaks and might be used to ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The DSB repair pathway is defective in FA, making it difficult to use HDR for mutation correction. Two groups have demonstrated that base editing can provide an effective method to correct mutations in the FANCA gene [35,36]. Hemophilia is a congenital hemorrhagic disease caused by mutations in coagulation factor VIII (FVIII) or factor IX (FIX).…”
Section: Hematological Disordermentioning
confidence: 99%
“…The DSB repair pathway is defective in FA, making it difficult to use HDR for mutation correction. Two groups have demonstrated that base editing can provide an effective method to correct mutations in the FANCA gene [35,36]. Hemophilia is a congenital hemorrhagic disease caused by mutations in coagulation factor VIII (FVIII) or factor IX (FIX).…”
Section: Hematological Disordermentioning
confidence: 99%
“… 51 Base editing can reach greater than 80% efficiency in HSPCs, and base-edited cells have shown engraftment similar to mock-treated cells, with no decrease in editing 16 weeks after xenotransplantation in mice. 50 , 52 , 53 , 54 Recently, prime editing efficiencies of 15%–40% in HSPCs has been reported without a decrease 17 weeks after xenotransplantation in mice. 55 Furthermore, base editing and prime editing have shown promising results for in vivo genome editing.…”
Section: Mitigation Of the P53-mediated Dna Damage Responsementioning
confidence: 99%
“…By fusing a catalytically dead Cas9 or a Cas9 nickase to different deaminases, it became possible to install transition mutations without generating DSBs (Komor et al, 2016;Gaudelli et al, 2017). Since, the continued evolution of BEs has increased efficacy, allowing the technology to be used in pre-clinical studies of ex vivo HSPC genome editing therapies for SCD and Fanconi anemia (Zeng et al, 2020;Newby et al, 2021;Siegner et al, 2022). However, while results so far seem promising, BEs are challenged by unwanted by-stander base conversions when multiple targetable cytosines or adenines are present at the target site, as well as both sgRNA-dependent and -independent off-target base conversions (Grünewald et al, 2019;Rees et al, 2019).…”
Section: In Vivo Prime Editing Of Hscs Is On the Horizonmentioning
confidence: 99%
“…Although these efforts have focused on in vitro use, previous work has demonstrated that delivery of mRNA-based genome editing tools can lead to efficient editing both ex vivo (De Ravin et al, 2016;Newby et al, 2021;Siegner et al, 2022) and in vivo (Musunuru et al, 2021;Rothgangl et al, 2021). Notably, two recent studies utilized lipid-nanoparticles (LNPs) to deliver mRNA-based adenine base editors to the liver of cynomolgus monkeys, achieving notably high editing rates (Musunuru et al, 2021;Rothgangl et al, 2021).…”
Section: Delivery Is the Keymentioning
confidence: 99%